2014
DOI: 10.5194/acp-14-12803-2014
|View full text |Cite
|
Sign up to set email alerts
|

On the hiatus in the acceleration of tropical upwelling since the beginning of the 21st century

Abstract: Abstract. Chemistry-climate models predict an acceleration of the upwelling branch of the Brewer-Dobson circulation as a consequence of increasing global surface temperatures, resulting from elevated levels of atmospheric greenhouse gases. The observed decrease of ozone in the tropical lower stratosphere during the last decades of the 20th century is consistent with the anticipated acceleration of upwelling. However, more recent satellite observations of ozone reveal that this decrease has unexpectedly stopped… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 57 publications
(99 reference statements)
1
19
0
Order By: Relevance
“…As shown in Figure , the strong hemispheric asymmetry with decreasing age in the SH and increasing age in the NH between 2002 and 2012 is clearly reflected in the integrated effect of mixing. Only below about 20 km the net mean age decrease coincides with decreasing RCTT, indicating an acceleration of the residual circulation in the lowest part of the stratosphere during 2002–2012, in agreement with Aschmann et al []. Remarkably, for the 1990–2013 period the residual circulation shows acceleration (negative RCTT trend) extending to higher altitudes (up to ∼26 km, Figure d), compared to the 2002–2012 period.…”
Section: Discussionsupporting
confidence: 90%
“…As shown in Figure , the strong hemispheric asymmetry with decreasing age in the SH and increasing age in the NH between 2002 and 2012 is clearly reflected in the integrated effect of mixing. Only below about 20 km the net mean age decrease coincides with decreasing RCTT, indicating an acceleration of the residual circulation in the lowest part of the stratosphere during 2002–2012, in agreement with Aschmann et al []. Remarkably, for the 1990–2013 period the residual circulation shows acceleration (negative RCTT trend) extending to higher altitudes (up to ∼26 km, Figure d), compared to the 2002–2012 period.…”
Section: Discussionsupporting
confidence: 90%
“…The trend is negative only in ERA-Interim at both altitudes (−3.9 % decade −1 at 440 K and −6.7 % decade −1 at 560 K). The estimated trends are statistically significant for the new data sets both at 440 and 560 K. Several recent studies have pointed out that AoA and BDC changes occur over timescales of several years to decades (Aschmann et al, 2014;Mahieu et al, 2014;Ray et al, 2014;Abalos et al, 2015;Poelger et al, 2015b). As summarized in Table 5, the upward mass flux at 440 K shows a strengthening trend during the first 22 years (1979-2000, +1.3 to +9.6 % decade −1 ), but a weakening trend (or slowing strengthening trend) during the last 12 years (2001-2012, −6.3 to +0.9 % decade −1 ) at 440 K in all data sets except for ERA-Interim.…”
Section: Mean-meridional Circulation (Mmc)mentioning
confidence: 64%
“…On the other hand, Aschmann et al . [] analyzed chemistry‐transport model simulations for the period between 1980 and 2013 and found that strengthening in tropical upwelling between 70 and 30 hPa ceased around 2002 and actually weakened between 2002 and 2013. Their results could partly explain the apparent inconsistency between our implied decreasing trend for the period of 2004–2014 and any increasing trends derived from longer‐term reanalysis data sets.…”
Section: Quasi‐biennial Oscillation Annual Modes and Interannual Vamentioning
confidence: 99%